2021
DOI: 10.3390/ani11113083
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Egg Quality of Laying Hens Fed Diets Containing Raw, Hydrobarothermally-Treated and Fermented Rapeseed Cake

Abstract: The present study was conducted to investigate how raw rapeseed cake (RRC), hydrobarothermally-treated rapeseed cake (HRC) and fermented rapeseed cake (FRC) fed to laying hens over a period of 12 weeks affected their performance, and the quality, fatty acid (FA) profile and oxidative stability of eggs. A total of 304 Hy-Line Brown laying hens at 36 weeks of age were distributed in a completely randomized design to four treatment groups with 38 replicates per treatment and two hens per replicate. The birds had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 71 publications
(87 reference statements)
0
10
0
Order By: Relevance
“…The effect of hydrobarothermal treatment and fermentation on the nutrient content of RC was partially described in our previous study (Kopacz et al, 2021), which demonstrated that the content of essential nutrients in RC was not affected by hydrobarothermal treatment or fermentation. However, the present study revealed that the applied processing methods affected the content of ANFs in RC.…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…The effect of hydrobarothermal treatment and fermentation on the nutrient content of RC was partially described in our previous study (Kopacz et al, 2021), which demonstrated that the content of essential nutrients in RC was not affected by hydrobarothermal treatment or fermentation. However, the present study revealed that the applied processing methods affected the content of ANFs in RC.…”
Section: Resultsmentioning
confidence: 82%
“…A decrease in the concentration of progoitrin is particularly important since the product of its degradation -goitrin can impair iodine metabolism in the body, leading to the deregulation of thyroid peroxidase and an enlargement of the thyroid gland (Keum et al, 2004). The beneficial influence of fermentation on the nutritional value of RC has been discussed in our previous articles (Drażbo et al, 2018;Kopacz et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonstarch polysaccharides increase the viscosity of the chyme, limiting the use of feed ingredients. Phytic acid forms complexes with minerals, reducing their bioavailability, while sinapine may be related to the appearance of a fishy egg taint in brown lines of laying hens ( Khajali and Slominski, 2012 ; Drażbo et al, 2019 ; Kopacz et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%